The effects of orthodontic tooth movement in endodontically treated teeth - Haque, Sabrina; Zakir, Mehreen (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
There are no relevant contraindications to orthodontic treatment of previously endodontically treated teeth, considering the quality of the obturated teeth, the health of the periodontal membrane, along with careful application of orthodontic force. Although, there is usually some degree of reversible or transient pulpal inflammation even in healthy teeth during orthodontic treatment, application of light and intermittent orthodontic force will reduce the risks provided sufficient time is given to allow proper repair of the dental tissue. However, there may be a few hazards associated with the treatment of endodontically involved teeth, some of which mainly include root resorption and ankylosis. This article will show some cases of teeth which had undergone root canal treatment prior to orthodontic management and further observed whether orthodontic tooth movement had caused any resorption in the root filled teeth. Root canal treated teeth can be moved orthodontically to the same extent as vital teeth, providing, a controlled force applica- tion to avoid risk of inflammatory root resorption. Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.12-15